2011
DOI: 10.1002/aic.12327
|View full text |Cite
|
Sign up to set email alerts
|

A multi‐scale theoretical model for gas–Liquid interface mass transfer based on the wide spectrum eddy contact concept

Abstract: On the basis of the wide spectrum eddy contact concept and the isotropic turbulence theory, a multi-scale theoretical model for the prediction of liquid-side mass transfer coefficient in gas-liquid system was developed. The model was derived from an unsteady-state convection and diffusion equation and considered the contributions of eddies with different sizes to the overall mass transfer coefficient. The proper contact time distribution at the surface is need to be determined to obtain satisfactory results wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…The proposed model (i.e., the unsteady‐state model presented in Table ) shows a good agreement with the experimental data. The results predicted by the model of Han et al is not shown in Figure as the predicted results are very close to those predicted by the model of Lamont and Scott . Furthermore, the models of Harriott (i.e., knormalL=1/[H/D+0.885tnormale/D]), Fortescue and Pearson (i.e., truek¯Λ=1.46DtrueU¯2/Λ) and Seo and Lee 11 (i.e., knormalL=0.9D 0teΦ(te)/tedte) are also not compared in this work since the parameters appearing in these models cannot be obtained directly from the known operating conditions.…”
Section: Resultssupporting
confidence: 52%
See 4 more Smart Citations
“…The proposed model (i.e., the unsteady‐state model presented in Table ) shows a good agreement with the experimental data. The results predicted by the model of Han et al is not shown in Figure as the predicted results are very close to those predicted by the model of Lamont and Scott . Furthermore, the models of Harriott (i.e., knormalL=1/[H/D+0.885tnormale/D]), Fortescue and Pearson (i.e., truek¯Λ=1.46DtrueU¯2/Λ) and Seo and Lee 11 (i.e., knormalL=0.9D 0teΦ(te)/tedte) are also not compared in this work since the parameters appearing in these models cannot be obtained directly from the known operating conditions.…”
Section: Resultssupporting
confidence: 52%
“…Then, λ e can be estimated by Eq. with a trial‐error method . That is, we can take different trial values of λ e from η to 2π/ n min and compare the turbulent energy dissipation rates calculated by Eq.…”
Section: Model Developmentmentioning
confidence: 99%
See 3 more Smart Citations